Effects of nutrition education, physical activity and motivational interviewing interventions on metabolic syndrome among females of reproductive age in Wakiso district, central Uganda: a randomised parallel-group trial - David Lubogo; Henry Wamani; Roy William Mayega; Christopher Garimoi Orach (BMC Public Health)
Abstract Background The prevalence of metabolic syndrome (MetS) has increased significantly in sub-Saharan African countries, including Uganda. Females are disproportionately affected by MetS compared to males. This study evaluated the effects of 12 weeks of community-based nutrition education (NE), physical activity (PA), and motivational interviewing (MI) interventions on MetS and its components among females of reproductive age in central Uganda. Methods We conducted a randomised parallel-group trial involving 120 females aged 15–49 years with MetS in Wakiso district, central Uganda. Participants were recruited between April and May 2023 and were randomly assigned to either the intervention (n = 60) or the control (n = 60) group. The 12-week intervention included NE, PA, and MI. The outcomes included changes in MetS and its components. Data were collected at baseline and endline using a modified STEPS questionnaire to assess sociodemographic factors, blood pressure (BP), waist circumference (WC), fasting blood glucose (FBG), triglycerides, HDL cholesterol (HDLC), and other variables. A generalised linear model was used to evaluate the impact of time and study groups on metabolic outcomes. Analyses were conducted using intention-to-treat in Stata (SE/14.0), at a p-value of < 0.05. Results The group x time interaction showed significant positive effects on MetS and its components at the endline. The intervention group had significantly lower odds of MetS compared to the control group [OR = 0.588, 95% CI (0.501, 0.690), p-value < 0.0001)]. The intervention showed reduced mean diastolic BP (coeff=-4.556, 95% CI (-9.035, -0.077), p-value = 0.046), reduced mean FBG (coeff=-1.012, 95% CI (-1.553, -0.470), p < 0.001), and increased mean HDLC (coeff = 0.139, 95% CI (0.015, 0.262), p-value = 0.028). Additionally, the intervention group had significantly higher odds of daily fruit and vegetable intake compared to the control group (OR = 6.31, 95% CI: 1.18–33.64,p = 0.031), increased moderate-intensity recreational activity (Coeff = + 155.65 min/week, 95% CI:19.11-292.22, p = 0.025) and reduced sedentary time by 43.94 min per day (Coeff= -43.94, 95% CI: -87.75 to– 0.13, p = 0.049). Conclusions The community-based interventions significantly improved MetS outcomes among females of reproductive age in Uganda. Scaling up this package of interventions should be explored. Trial registration ISRCTN, ISRCTN17445597. Registered 06 June 2024 - Retrospectively registered, https://www.isrctn.com/ISRCTN17445597 .